Repertoire Analysis of B-Cells Located in Striated Ducts of Salivary Glands of Patients With Sjögren's Syndrome - Visser, Annie; Verstappen, Gwenny M.; van der Vegt, Bert; Vissink, Arjan; Bende, Richard J.; Bootsma, Hendrika; Bos, Nicolaas A.; Kroese, Frans G. M. (Frontiers in Immunology, 2020)
A major complication of primary Sjögren’s syndrome (pSS) is development of mucosa associated lymphoid tissue (MALT) B-cell lymphoma, particularly in salivary glands. These lymphomas express FcRL4 and are characteristically associated with lymphoepithelial lesions. Neoplastic B-cells may be derived from non-neoplastic glandular intraductal B-cells, also virtually all expressing FcRL4. A characteristic feature of MALT lymphomas is the production of rheumatoid factors (RFs), which are largely encoded by stereotypic immunoglobulin variable heavy chain (IGHV) sequences. The aim of this study was to examine whether there is a relationship between the intraductal and periductal B-cells and whether the intraductal B-cells are selected for RF. RNA was extracted from laser-microdissected infiltrated ductal areas and periductal infiltrates from frozen parotid gland tissue sections of 5 pSS patients. PCR amplified IGHV transcripts were cloned into pCR™4-TOPO vector and subsequently sequenced. Microdissected ducts yielded 96 unique IGHV sequences derived from intraductal B-cells, while 119 unique IGHV sequences were obtained from periductal infiltrates. No major difference in VH-gene usage was observed between intraductal and periductal B-cells. Nearly all (>90%) IGHV sequences derived from both intraductal and periductal B-cells were mutated. Clonal expansions as defined by shared VDJ rearrangements were also present among both intraductal and periductal B-cells: in total 32 clones were found, from which 12 were located within ducts, 15 in periductal areas and 5 clones shared members in both areas. We observed 12 IGHV rearrangements encoding for RF sequences from which 2 were derived from intraductal B-cells and 10 from periductal B-cells. Nine RF sequences were part of a clone. Together these findings indicate that intraductal and periductal B-cells are closely related to each other. Intraductal B-cells are most likely derived from periductal B-cells. We did not obtain evidence that RF-specific B-cells are enriched within the striated ducts. We speculate that in principle any activated B-cell can enter the striated ducts from the periductal infiltrate, irrespective of its antigenic specificity. Within the ducts, these B-cells may receive additional activation and proliferation signals, to further expand at these sites and by acquisition of driver-mutations develop towards lymphoma.